The Global Epidemiology of RSV in Community and Hospitalized Care: Findings From 15 Countries. (30th March 2021) - Staadegaard, Lisa; Caini, Saverio; Wangchuk, Sonam; Thapa, Binay; de Almeida, Walquiria Aparecida Ferreira; de Carvalho, Felipe Cotrim; Njouom, Richard; Fasce, Rodrigo A; Bustos, Patricia; Kyncl, Jan; Novakova, Ludmila; Caicedo, Alfredo Bruno; et al.
Abstract: Background: Respiratory syncytial virus (RSV) is one of the leading causes of acute respiratory tract infections. To optimize control strategies, a better understanding of the global epidemiology of RSV is critical. To this end, we initiated the Global Epidemiology of RSV in Hospitalized and Community care study (GERi). Methods: Focal points from 44 countries were approached to join GERi and share detailed RSV surveillance data. Countries completed a questionnaire on the characteristics of their surveillance system. Results: Fifteen countries provided granular surveillance data and information on their surveillance system. A median (interquartile range) of 1641 (552–2415) RSV cases per season were reported from 2000 and 2020. The majority (55%) of RSV cases occurred in the <1-year-olds, with 8% of cases reported in those aged ≥65 years. Hospitalized cases were younger than those in community care. We found no age difference between RSV subtypes and no clear pattern of dominant subtypes. Conclusions: The high number of cases in the <1-year-olds indicates a need to focus prevention efforts in this group. The minimal differences between RSV subtypes and their co-circulation implies that prevention needs to target both subtypes. Importantly, there appears to be a lack of RSV surveillance data in the elderly.